2019
DOI: 10.3346/jkms.2019.34.e68
|View full text |Cite
|
Sign up to set email alerts
|

Addition of Cervical Elastography May Increase Preterm Delivery Prediction Performance in Pregnant Women with Short Cervix: a Prospective Study

Abstract: Background We investigated whether there is a difference in elastographic parameters between pregnancies with and without spontaneous preterm delivery (sPTD) in women with a short cervix (≤ 25 mm), and examined the ability of elastographic parameters to predict sPTD in those women. Methods E-Cervix TM (WS80A; Samsung Medison, Seoul, Korea) elastography was used to examine the cervical strain. Elastographic parameters were compared between preg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 39 publications
2
31
0
Order By: Relevance
“…In addition, the strain was always depicted in a color map generated by a semiquantitative analysis based on a scoring method . Based on Park's study, our study used a new semiautomatic tool, E‐Cervix, to measure the stiffness of the cervix during pregnancy; this tool was used to evaluate the whole cervix as an ROI and outline the specific areas of the IOS and EOS at the same time to obtain multiple quantitative elastic parameters and the CL. In addition, the strain calculation made by E‐Cervix only starts when there are enough consecutive steady frames to provide sufficient data, and the reliability indicator plays an important role in excluding inadvertent movements by the operator or fetus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the strain was always depicted in a color map generated by a semiquantitative analysis based on a scoring method . Based on Park's study, our study used a new semiautomatic tool, E‐Cervix, to measure the stiffness of the cervix during pregnancy; this tool was used to evaluate the whole cervix as an ROI and outline the specific areas of the IOS and EOS at the same time to obtain multiple quantitative elastic parameters and the CL. In addition, the strain calculation made by E‐Cervix only starts when there are enough consecutive steady frames to provide sufficient data, and the reliability indicator plays an important role in excluding inadvertent movements by the operator or fetus.…”
Section: Discussionmentioning
confidence: 99%
“…From this image and the ROI, it is possible to extract many meaningful parameters that represent the overall cervix and specific areas of the IOS and EOS. Only one study has used this tool, and the results indicated that it may improve the ability to predict spontaneous preterm delivery in women with a short CL between 1.5 and 2.5 cm . In addition, its feasibility and reproducibility for use in cervical assessments during pregnancy has not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…2 shows examples of a short cervix as measured on cervical elastography using the E cervix program, showing relatively low, intermediate, and high strain values. We checked 5 elastographic parameters, namely, the strain of the internal os of the cervix (IOS), external os of the cervix (EOS), ratio of the strain of the internal and external os (ratio [IOS/EOS]), elasticity contrast index (ECI), and hardness ratio, as previously defined [7], as well as cervical length.…”
Section: Roi Region Of Interest A)mentioning
confidence: 99%
“…In strain elastography a mechanical force is manually applied to cause the displacement of tissues and in shear wave elastography an acoustic force creates a mechanical impulse that induces displacement of tissues in the form of shear-waves [ 95 ]. The usefulness in obstetrics has been investigated for the cervix [ 96 ], specifically to attempt and predict preterm labor [ 97 ], and the placenta [ 98 ] and in abnormal placental invasion to differentiate between placenta accreta spectrum (formerly known as morbidly adherent placenta) [ 99 ].…”
Section: The Future (It’s Almost Here)mentioning
confidence: 99%